Integration of a real‐time tumor monitoring system into gated proton spot‐scanning beam therapy: An initial phantom study using patient tumor trajectory data. Issue 7 (26th June 2013) - Matsuura, Taeko; Miyamoto, Naoki; Shimizu, Shinichi; Fujii, Yusuke; Umezawa, Masumi; Takao, Seishin; Nihongi, Hideaki; Toramatsu, Chie; Sutherland, Kenneth; Suzuki, Ryusuke; Ishikawa, Masayori; Kinoshita, Rumiko; et al.
Abstract : Purpose: : In spot‐scanning proton therapy, the interplay effect between tumor motion and beam delivery leads to deterioration of the dose distribution. To mitigate the impact of tumor motion, gating in combination with repainting is one of the most promising methods that have been proposed. This study focused on a synchrotron‐based spot‐scanning proton therapy system integrated with real‐time tumor monitoring. The authors investigated the effectiveness of gating in terms of both the delivered dose distribution and irradiation time by conducting simulations with patients' motion data. The clinically acceptable range of adjustable irradiation control parameters was explored. Also, the relation between the dose error and the characteristics of tumor motion was investigated. Methods: : A simulation study was performed using a water phantom. A gated proton beam was irradiated to a clinical target volume (CTV) of 5 × 5 × 5 cm 3, in synchronization with lung cancer patients' tumor trajectory data. With varying parameters of gate width, spot spacing, and delivered dose per spot at one time, both dose uniformity and irradiation time were calculated for 397 tumor trajectory data from 78 patients. In addition, the authors placed an energy absorber upstream of the phantom and varied the thickness to examine the effect of changing the size of the Bragg peak and the number of required energy layers. The parameters with which 95% of the tumor trajectory data fulfill our defined criteria were accepted. Next, correlation coefficients were calculated between the maximum dose error and the tumor motion characteristics that were extracted from the tumor trajectory data. Results: : With the assumed CTV, the largest percentage of the data fulfilled the criteria when the gate width was ±2 mm. Larger spot spacing was preferred because it increased the number of paintings. With a prescribed dose of 2 Gy, it was difficult to fulfill the criteria for the target with a very small effective depth (the sum of an assumed energy absorber's thickness and the target depth in the phantom) because of the sharpness of the Bragg peak. However, even shallow targets could be successfully irradiated by employing an adequate number of paintings and by placing an energy absorber of sufficient thickness to make the effective target depth more than 12 cm. The authors also observed that motion in the beam direction was the main cause of dose distortion, followed by motion in the lateral plane perpendicular to the scan direction. Conclusions: : The results suggested that by properly adjusting irradiation control parameters, gated proton spot‐scanning beam therapy can be robust to target motion. This is an important first step toward establishing treatment plans in real patient geometry.